1995
DOI: 10.1080/00102209508907739
|View full text |Cite
|
Sign up to set email alerts
|

Gasdynamic Abatement of NOxEmission from Industrial Natural Gas Jet Diffusion Flames

Abstract: The aim of this research was to examine the possibilities of NO, emission abatement from high temperature industrial furnaces by controlling the gasdynamic parameters of natural gas flames. Thc following parameters were investigated: air and gas velocity at burner exit, air swirl angle, position of the burner nozzles and air staging. It has been shown that moderateswirling ofthecombustion air enhances the level of NO,, the lowest NO, emissions are observed for parallel air and gas flow burners. It is also demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…On the other hand, passive techniques to manipulate the flow dynamics and rates of mixing of reactants in the combustion zone have been the focus of research in the last decade. The application of nonaxisymmetric burner-exit geometries [3][4][5], staging of fuel-air mixing [6], swirl burners [7,8], as well as venturi-cascading [9,10] are examples of such techniques. "Venturi-cascading" technique was developed by Qubbaj and Gollahalli [9,10] in the last three years.…”
Section: A Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, passive techniques to manipulate the flow dynamics and rates of mixing of reactants in the combustion zone have been the focus of research in the last decade. The application of nonaxisymmetric burner-exit geometries [3][4][5], staging of fuel-air mixing [6], swirl burners [7,8], as well as venturi-cascading [9,10] are examples of such techniques. "Venturi-cascading" technique was developed by Qubbaj and Gollahalli [9,10] in the last three years.…”
Section: A Introductionmentioning
confidence: 99%
“…Previous studies have reported significant improvements in the combustion and emission characteristics of combustion systems utilizing swirl flow configurations [7,8,[11][12][13][14].…”
Section: A Introductionmentioning
confidence: 99%